(untitled) (Conference on English Language Teaching, 2025)
This study investigates the phonological challenges encountered by multilingual learners in Medan during the process of second language acquisition (SLA), with a specific focus on English as the target language. Drawing on the theoretical frameworks of Generative Phonology and Optimality Theory (OT), this research analyzes the influence of the learners’ first and second languages—predominantly Bahasa Indonesia and regional languages such as Batak and Minangkabau—on their English phonological output. Focusing on voiced and voiceless consonants, the study identifies common patterns of interference, including devoicing, fronting, and stopping. Data were collected from ten participants aged 7 to 15 years through a reading task comprising English words containing target consonants. The findings revealed systematic deviations, such as /ʃ/ → /s/, /z/ → /s/, /v/ → /f/, and /θ/ → /t/, reflecting the influence of native phonological rules on English pronunciation. The study applies Generative Phonology and Optimality Theory to analyze these patterns, offering insights into the processes underlying the interference. Results demonstrate that the learners simplify or substitute challenging sounds based on their linguistic background, highlighting the impact of native phonological systems. The study concludes that both universal markedness and language-specific constraints play crucial roles in shaping L2 phonology in a multilingual context. Implications for pronunciation teaching and curriculum design are also discussed, emphasizing the need for context-sensitive pedagogical strategies in multilingual regions like Medan.